Construct validity in TOEFL iBT speaking tasks: Insights from natural language processing. (July 2016) - Kyle, Kristopher; Crossley, Scott A.; McNamara, Danielle S.
This study explores the construct validity of speaking tasks included in the TOEFL iBT (e.g., integrated and independent speaking tasks). Specifically, advanced natural language processing (NLP) tools, MANOVA difference statistics, and discriminant function analyses (DFA) are used to assess the degree to which and in what ways responses to these tasks differ with regard to linguistic characteristics. The findings lend support to using a variety of speaking tasks to assess speaking proficiency. Namely, with regard to linguistic differences, the findings suggest that responses to performance tasks can be accurately grouped based on whether a task is independent or integrated. The findings also suggest that although the independent tasks included in the TOEFL iBT may represent a single construct, responses to integrated tasks vary across task sub-type.